2014
DOI: 10.1080/13596748.2014.955364
|View full text |Cite
|
Sign up to set email alerts
|

Responding to the mental health and well-being agenda in adult community learning

Abstract: In the United Kingdom, changes in the policy, funding and commissioning landscape for mental health and well-being are posing opportunities and challenges for adult community learning (ACL). Opportunities include increased recognition of, and funding for, the 'wider benefits' of learning, whereas challenges include the risks of ACL provision becoming hijacked by a health and well-being agenda that compromises its primary educational purpose and values. This paper engages with these policy debates through repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“…Many of the findings in this study resonate with previous work in this area (Fernando et al, 2014;James and Talbot-Strettle, 2009;Lewis, 2014). The findings confirmed that while adults with mental health problems may encounter barriers to taking part in adult education, being able to engage with a curriculum through supportive teaching, positively influenced their sense of wellbeing.…”
Section: Prior Researchsupporting
confidence: 88%
“…Many of the findings in this study resonate with previous work in this area (Fernando et al, 2014;James and Talbot-Strettle, 2009;Lewis, 2014). The findings confirmed that while adults with mental health problems may encounter barriers to taking part in adult education, being able to engage with a curriculum through supportive teaching, positively influenced their sense of wellbeing.…”
Section: Prior Researchsupporting
confidence: 88%
“…For example, in adult and community education and access to higher education programmes, some radical/critical educators look to the work of Amyrta Sen, to propose an assets-based or capability approach (eg Walker 2012, Lewis 2012. For example, advocates of programmes in adult and community education that aim to develop mental health and wellbeing, propose that, "agency is … one's ability to pursue goals that one values and that are important for the life an individual wishes to lead; agency and well-being are deeply connected" and therefore essential for mental health (Lewis 2012(Lewis , 2014. Here, educational forms of recognition aim to redress cultural, symbolic and status injustices, and the emotional and psychological harms caused by "non-recognition, the rendering of invisibility as a result of dominant cultural forms; misrecognition, being seen as lacking value and as inferior; and disrespect, being maligned or disparaged in everyday interactions or representations" (Lewis, 2009: 259).…”
Section: The Therapisation Of Social Justicementioning
confidence: 99%
“…In Britain, diverse educational settings, including youth work, youth educational programmes, transitions and rehabilitation projects, adult and community education, have introduced initiatives such as circle time, lessons in emotional education, psychodrama workshops and anger management. These supplement counselling-based peer mentoring and lifecoaching as part of wholeinstitution support systems Hayes 2009, Ecclestone andLewis 2014, see also Watson et al 2012). In eclectic and ad hoc ways, some initiatives adapt elements from Cognitive Behavioural Therapy (CBT), positive psychology and individually-based diagnoses of emotional needs or behaviour problems.…”
Section: Introductionmentioning
confidence: 99%
“…Outside these varying levels of professional training, experience of certain difficult experiences can legitimise more rudimentary forms of expertise in the form of being a 'wounded healer': for example, the Amy Winehouse Foundation, a charity funded by the Lottery to promote 'resilience training' in schools, proclaims facilitators' own recovery from drug and drink problems as sufficient expertise to carry out psycho-emotional assessments of young people's resilience and to run 'resilience and self-esteem building sessions in response to those assessments (Rawdin forthcoming). Again this resonates with other educational settings such as adult and community education, successful survivor and user campaigns in mental health to de-centre expertise and thereby de-stigmatise mental illness reinforces a shift from specialist intervention towards peer-based strategies and the use of 'embedded' pedagogies for wellbeing in mainstream programmes rather than targeted or discrete ones (see Lewis, 2014;Lewis et al, 2015).…”
Section: New Types Of Psy-expertsmentioning
confidence: 99%
“…It is not surprising, then, that expanding official descriptors and criteria for assessment are linked inextricably to many diverse references to vulnerability in everyday institutional and personal life, ranging from exposure to serious structural and social problems to assumed harms and risks from mundane, everyday experiences and relationships (e.g. Ecclestone & Lewis, 2014). Here, for example, the Office for Standards in Education endorses these diffused meanings, defining migrant children, those with special educational needs, pupils who are disengaged or who are simply not meeting their targets as vulnerable (OfSTED, 2012).…”
Section: The Rise Of a 'Vulnerability Zeitgeist'mentioning
confidence: 99%